1998
DOI: 10.1021/ac980230k
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Dye DNA Sequencing in Capillary Gel Electrophoresis by Diode Laser-Based Time-Resolved Fluorescence Detection

Abstract: A new one-lane, four-dye DNA sequencing method was developed which is based on time-resolved detection and identification of fluorescently labeled primers. For fluorescent labels, we used two newly synthesized rhodamine derivatives (MR200-1, JA169), a new oxazine derivative (JA242), and a commercially available cyanine dye (CY5). The dye fluorescence was excited by a pulsed diode laser emitting at 630 nm. The fluorescence decay was detected by an avalanche photodiode using a single-filter system. The dyes used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 43 publications
2
91
0
2
Order By: Relevance
“…44 An important characteristic of the detection dye in this context is that the excitation maximum of the dye^nucleic acid complex should be close to an available laser wavelength. Stains used in CE include SYBR 1 Oxazine derivative JA242 80 Platinum coproporphyrin 81,82 Rhodamine derivatives MR200-1 and JA169 80 5-Carboxyrhodamine (RHD) 83 Rhodamine green 29 Carboxy-X-rhodamine (ROX) 59,75 Carboxytetramethylrhodamine (TAMRA) 59 Tetrachloro-6-carboxy uorescein (TET) 83 Texas Red …”
mentioning
confidence: 99%
“…44 An important characteristic of the detection dye in this context is that the excitation maximum of the dye^nucleic acid complex should be close to an available laser wavelength. Stains used in CE include SYBR 1 Oxazine derivative JA242 80 Platinum coproporphyrin 81,82 Rhodamine derivatives MR200-1 and JA169 80 5-Carboxyrhodamine (RHD) 83 Rhodamine green 29 Carboxy-X-rhodamine (ROX) 59,75 Carboxytetramethylrhodamine (TAMRA) 59 Tetrachloro-6-carboxy uorescein (TET) 83 Texas Red …”
mentioning
confidence: 99%
“…1 For example, for 'conventional' DNA sequencing by the Sanger method, the electrophoresis within a capillary or slab gel may be multiplexed by the use of spectroscopically identifiable fluorescent labels. Lieberwirth et al 2 have recently demonstrated such multiplex dye DNA sequencing in capillary gel electrophoresis by the use of four dyes with disparate fluorescence lifetimes. The best algorithm for classification was found to be "a special pattern recognition technique" , which is equivalent to the maximum likelihood estimation (MLE) technique3 described in section 3.…”
Section: Intr0:ducti0nmentioning
confidence: 99%
“…To compare P(m3 A) and P(m3 fB) we need only compare the ratio P(mjIA)/P(mIB) = H(aj//3j)mi (2) with 1, or the logarithm of the ratio ln[P(mIA)/P(mIB)] = mln(a//3) (3) with 0.…”
Section: Maximum Likelihood Categorizationmentioning
confidence: 99%
“…Among several modes of separation, CGE has been extensively employed since the gel matrix provides the capability of sieving for different sizes of DNA fragments. 15 CGE has been extensively employed for the study of DNA sequencing, 16 DNA restriction fragment analysis, 17 and polymerase chain reaction (PCR) fragment analysis. 18 In CGE, one-or four-base resolution was easily obtained by the proper choice of gel matrix and concentration.…”
Section: Introductionmentioning
confidence: 99%